Analisis Problematika Guru dalam Mengintegrasikan Pembelajaran Biologi dan Islam di Madrasah Aliyah Negeri Se-Kota Padang - Syahra Fadilla; Ardi Ardi (Al-Alam: Islamic Science Education Journal, 2025)
The integration of Biology learning and Islamic values is a distinctive feature of Madrasah Aliyah; however, its implementation has not been optimal. This study aims to analyze the problems faced by Biology teachers in integrating Biology and Islamic values Madrasah Aliyah Negeri in Padang City. A quantitative descriptive approach was employed involving all 11 Biology teachers. Data were collected using a closed-ended questionnaire covering integrative pedagogical competence, instructional planning and implementation, learning resources, institutional support, and professional development. Data were analyzed using descriptive quantitative techniques based on mean scores. The results indicate that the problems remain high, with mean scores of 17.57 for teachers’ competence, 18.09 for instructional implementation, and 20.33 for system and resource support, all categorized as problematic. These findings indicate that the integration of Biology and Islamic values has not been optimally implemented and requires improvements in teachers’ competence, instructional practices, and institutional support.